THE MAIN WAYS OF DEVELOPING SPEAKING SKILLS (Academicia Globe: Inderscience Research, 2023)
This article highlights role-plays, discussions, informal conversations, debates, presentations and interviewing as the main and wide-spread ways of developing speaking skills among language learners.